Hierarchical aging pathways and reversible fragile-to-strong transition upon annealing of a metallic glass former. (1st February 2018) - Gallino, Isabella; Cangialosi, Daniele; Evenson, Zach; Schmitt, Lisa; Hechler, Simon; Stolpe, Moritz; Ruta, Beatrice
Abstract: The change of physical properties during aging and the associated microscopic dynamics of the Au49 Cu26.9 Si16.3 Ag5.5 Pd2.3 bulk metallic glass are investigated using a broad collection of laboratory and synchrotron-based techniques, such as differential- and fast-scanning calorimetry, thermomechanical testing, and x-ray photon correlation spectroscopy. We observe multiple decays in the enthalpy change during aging. This is reflected by a microscopic ordering consisting of distinct stationary dynamical regimes interconnected by abrupt aging processes. The stationary regimes are representative of states of local and transient equilibrium with increasingly higher activation energies. Furthermore, the aging study is conducted with the kinetically fragile frozen-in structure and the underlying fragile-to-strong transition is accessed by the ultra-viscous liquid state during annealing on a long-time scale and corresponds to the last observed enthalpy equilibration decay. The experimental work verifies, for the first time, that in a metallic glass forming system, the fragile-to-strong transition can also occur below the conventional glass transition temperature. Upon reheating, the reverse transformation, i.e. the strong-to-fragile transition, is observed with an entropy change of 0.19 J/(g-atom K), which is 2.4% of the entropy of fusion. Graphical abstract: Image 1